PD‐1 inhibitors for non‐small cell lung cancer patients with special issues: Real‐world evidence. (6th February 2020) - Byeon, Seonggyu; Cho, Jang Ho; Jung, Hyun Ae; Sun, Jong‐Mu; Lee, Se‐Hoon; Ahn, Jin Seok; Park, Keunchil; Ahn, Myung‐Ju
Abstract: Background: Immune checkpoint inhibitors (ICIs) have provided new therapeutic options for non‐small cell lung cancer(NSCLC) patients. However, due to concerning increases in immune‐related adverse events, clinical trials usually exclude patients with special issues such as viral hepatitis, tuberculosis (Tbc), interstitial lung disease (ILD) and autoimmune disease. Methods: We retrospectively reviewed the medical records of NSCLC patients who received ICIs, and analyzed the clinical outcomes of patients with special issues. Results: Between January 2015 and October 2018, 237 patients received ICIs. Of these patients, 26% (61/237) had special issues: 32 had hepatitis B viral (HBV) infections, 20 Tbc, six ILD, one HIV infection, one Behçet's disease and a past HBV infection, and one rheumatoid arthritis. The incidence of hepatitis tended to be higher in patients with HBV infections than in those without (18.8% vs 8.91%, P = .082). Severe hepatitis (grade 3 or higher) was more common in HBV‐infected patients (12.5% vs 1.9%, P = .0021), but the AEs were well‐managed. During ICI treatment, three of the 20 patients with a history of pulmonary Tbc developed active pulmonary Tbc, considered reactivations. No aggravation of ILD was noted. One RA patient experienced a disease flare and was treated with a low‐dose steroid. There was no significant difference in the overall response rate or progression‐free survival between patients with and without special issues. Conclusion: Given the relatively low incidence of immune‐related AEs and the comparability of clinical outcomes, ICIs can be treatment option of NSCLC patients with special issues. Abstract : Given the relatively low incidence of immune‐related AEs and the comparability of clinical outcomes, ICIs can be treatment option of NSCLC patients with special issues.